Optimum design of 3D reinforced concrete frames using DMPSO algorithm. (January 2018) - Esfandiari, M.J.; Urgessa, G.S.; Sheikholarefin, S.; Manshadi, S.H. Dehghan
Highlights: An algorithm optimization of real-world 3D reinforced concrete frames using the multi-criterion Decision Making and Particle Swarm Optimization (DMPSO) algorithm. The algorithm was shown to lead to feasible optimal designs, while also taking advantage of infeasible designs during the optimization procedure. The optimum design obtained by the DMPSO algorithm is directly ready for practical application without the need of any further modification or processing. Abstract: Evolutionary optimization algorithms are widely used for solving optimization problems. However, in the realm of real-world structures finding the optimum design would be difficult and time-consuming due to large number of design variables, enormous size of the search space, and availability of numerous constraints. As a result, holistic optimization approaches that consider architectural and other practical requirements in addition to required code provisions are rather limited in real-world structures. This paper presents an innovative algorithm combining multi-criterion decision-making (DM) and Particle Swarm Optimization (PSO), which is called DMPSO, for accelerating convergence toward optimum solution in 3D reinforced concrete (RC) frames. All practical requirements are considered for obtaining directly constructible designs without any further modifications. The effectiveness of the proposed algorithm is illustrated in optimization of 3D RC frames subjected to lateral seismic forces according to ASCE 7 requirements. The results confirm the ability of the proposed DMPSO algorithm to efficiently find optimal solutions for 3D RC optimization problems.